2023
DOI: 10.1002/cl2.1316
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions for improving social inclusion outcomes for people with disabilities in low‐ and middle‐income countries: A systematic review

Abstract: Background People with disabilities—more than a billion people worldwide—are frequently excluded from social and political life, and often experience stigmatising attitudes and behaviours from people without disabilities. This stigma, coupled with inaccessible environments and systems and institutional barriers (e.g., lack of inclusive legislation), may result in discrimination against people with disabilities (and their families) to the degree that they are not able to enjoy their rights on an equal basis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“… 25 , 26 , 27 Moreover, there also needs to be a particular focus on LMICs as data is lacking. 28 , 29 , 30 , 31 The focus on LMICs is crucial as 80% of people with disabilities reside in these countries. The level of exclusion, such as from schools, is likely to be particularly high in these settings, where health systems are also weaker.…”
Section: Introductionmentioning
confidence: 99%
“… 25 , 26 , 27 Moreover, there also needs to be a particular focus on LMICs as data is lacking. 28 , 29 , 30 , 31 The focus on LMICs is crucial as 80% of people with disabilities reside in these countries. The level of exclusion, such as from schools, is likely to be particularly high in these settings, where health systems are also weaker.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ADL disability can impact psychological factors like self-esteem and social skills, indirectly affecting muscle health. Overall, addressing ADL capacity holistically is crucial for preventing and treating sarcopenia, requiring targeted interventions to improve muscle health and quality of life [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently shown that children with autism often face barriers to inclusion in educational, recreational, and social activities due to stigma, discrimination, and lack of understanding from their peers and community members. Occupational therapists can work collaboratively with schools, community organizations, and families to promote acceptance, create inclusive environments, and facilitate meaningful social interactions for children with autism, said by Saran (2023).…”
Section: The Role Of Sociology In Occupational Therapy Interventions ...mentioning
confidence: 99%